The beneficial effect of resveratrol on rat bladder contractility and oxidant damage following ischemia/reperfusion - ERCAN, FERİHA; ŞENER, GÖKSEL (KARGER, 2006)
Objective: The present study aimed to investigate the possible beneficial activities of resveratrol (3,5,4'-trans-trihydroxystilbene), a natural phytoalexin, on contractility and oxidant damage after ischemia/reperfusion (I/R) of the rat urinary bladder. Materials and Methods: The abdominal aorta of Sprague-Dawley rats was occluded for 60 min to induce ischemia and then allowed 60 min of reperfusion. Resveratrol (10 mg/kg) or saline was administered intraperitoneally 15 min before ischemia and immediately before reperfusion. In the sham-operated group, the abdominal aorta was left intact and the animals were treated with resveratrol or saline. The bladder samples were either used for functional studies or stored for biochemical assays. Results: In the I/R group, the isometric contractile responses of the bladder strips to carbachol (CCh; 10(-8)-10(-4) mol/l) were lower than those of the control group and were reversed by treatment with resveratrol. Histological evaluation revealed loss of urothelial cells, detachment and loss of urothelial cells and local ulcerated areas and severe inflammatory cell infiltration in the untreated I/R group, and regeneration of luminal mucosa and a significant decrease in the density of the inflammatory cell population in the resveratrol-treated I/R group. Lipid peroxidation and the myeloperoxidase activity of the bladder tissues in the I/R group were higher than in the sham-operated group. Resveratrol treatment in the I/R group decreased these parameters compared with I/R alone. Similarly, the significant decrease in tissue glutathione level in the I/R group compared with controls was also prevented by resveratrol. Conclusion: Treatment with resveratrol almost completely reversed the low contractile responses of the rat urinary bladder to CCh and prevented oxidative tissue damage following I/R. Copyright (c) 2006 S. Karger AG, Basel.
Keywords: bladder contractility; ischemia/reperfusion; oxidants; resveratrol; WINE CONSTITUENT POLYPHENOL; RABBIT URINARY-BLADDER; RED WINE; OUTLET OBSTRUCTION; NITRIC-OXIDE; ISCHEMIA; CARDIOPROTECTION; STIMULATION; EXPRESSION; MECHANISM